2016
DOI: 10.21276/aimdr.2017.3.1.mb1
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Typing of Methicillin Resistant Staphylococcus aureus and Changing Trend in their Antibiotic Profile

Abstract: Background: Increasing prevalence of Methicillin-resistant Staphylococcus aureus (MRSA), a major pathogen in both health care facilities and community, is an escalating public health concern. Knowledge of prevalence of MRSA and their current antimicrobial profile becomes necessary in the selection of appropriate empirical treatment of these infections. Aims & Objectives: To estimate the prevalence of MRSA & to evaluate its antibiotic sensitivity pattern and to determine Bacteriophage typing for epidemiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…However, a study has demonstrated that phage typing can be helpful in the epidemiological surveillance and outbreak investigation of MDR Salmonella Typhimurium [89]. In addition to S. Typhimurium, a set of 23 phages was also used in the phage typing of MRSA for epidemiological monitoring, with a majority of the MRSA strains (84%) proving to be typable [90]. Furthermore, phage typing in conjunction with antibiotic susceptibility testing has also been shown to facilitate in the identifying of different strains of MDR K. pneumoniae that co-occur at an infection site [91].…”
Section: Clinical Mdr Bacterial Treatmentmentioning
confidence: 99%
“…However, a study has demonstrated that phage typing can be helpful in the epidemiological surveillance and outbreak investigation of MDR Salmonella Typhimurium [89]. In addition to S. Typhimurium, a set of 23 phages was also used in the phage typing of MRSA for epidemiological monitoring, with a majority of the MRSA strains (84%) proving to be typable [90]. Furthermore, phage typing in conjunction with antibiotic susceptibility testing has also been shown to facilitate in the identifying of different strains of MDR K. pneumoniae that co-occur at an infection site [91].…”
Section: Clinical Mdr Bacterial Treatmentmentioning
confidence: 99%